Cooking from the spirit : easy, delicious, and joyful plant-based inspirations - Brown, Tabitha (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"Tabitha Brown, the #1 New York Times bestselling author of Feeding the Soul, presents her first cookbook-full of easy, family-friendly vegan recipes and stories from the spirit, inspired by her health journey and love of delicious food"--